THE REALISM OF AESTHETICS AS THE NEAREST IMAGE OF GOD: A Liberated Ideology in the Islamic Aesthetics - Gunawan Adnan; Widiarto Widiarto; Wilaela Wilaela (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
The measurement of beauty might be a problem when a person claimed about the value of beauty. This had brought the issue of Islamic aesthetics (which was expressed in the works of art), less appreciated and mired in the stagnation for centuries. While in the West, the aesthetic value had been trapped in the dichotomy of subjectivity and objectivity and had led to the relativistic subjectivity by marginalizing metaphysical approach. Polarization of Islamic aesthetics on geometric themes, arabas and calligraphy had put the creativity of Muslim artists in the stocks, even up to the understanding of the aesthetic itself. Iconoclastic of the mainstream of Islamic artistic should have been one option only. As a product of classical thought and compliance, the iconoclastic should have no longer been representing the needs and been existing in the present context. This study was trying to make arguments both longstanding and recent findings. Realism became researchers’ choice, because realism had the richest footing both in the Qur’an and scientific findings. This study expected to break the shell of orthodoxy about the size of aesthetics in the frame of Islam and gave hope to both the perpetrators and the art connoisseur to the ultimate point